Analyzing results of proficiency tests carried out by the FGBI ARRIAH reference laboratory for FMD diagnosis in 2013-2015 - N. N. Lugovskaya; S. R. Kremenchugskaya (Ветеринария сегодня)
Results of the international interlaboratory proficiency tests on FMD diagnosis carried out by the FGBI ARRIAH Reference Laboratory for FMD Diagnosis in 2013-2015 were analyzed. Ten laboratories from seven CIS-countries took part in the proficiency tests, including the Republic of Kazakhstan, the Republic of Armenia, the Republic of Moldova, the Republic of Belarus, the Republic of Azerbaijan, the Republic of Tajikistan, the Kyrgyz Republic and five laboratories of the FGBI «ARRIAH».